A new cryopathic syndrome. Issue 9 (September 1980) - Caudron, M; Bieva, C; Laurent, E; De Meuter, F; Feremans, W W; Lebas, P; Malmendier, C L
Abstract : One case of a syndrome simulating a systemic disease is reported. An HLA-B, patient presented with apparent toxoplasmosis, retinal vein occlusion, autoantibodies against cephalin, contact factors and lipoproteins, immune complexes, rheumatoid factor, and cryoprecipitate. A representation of the immunological mechanisms involved is proposed.